The Determinants of Human Resource Disclosures in ASEAN - Adila, Arina; Wahyuningrum, Indah Fajarini Sri (Universitas Negeri Semarang, 2021)
This paper aims to determine the level of Human Resource Disclosure (HRD) in ASEAN and to examine the impact of firm size, firm age, auditor type, profitability, board size, and gender on HRD. The population of this study was banking companies listed on the Indonesian Stock Exchange (IDX), Philippines Stock Exchange (PSE), The Stock Exchange of Thailand (SET), Bursa Malaysia (Bursa), and Singapore Exchange (SGX) in 2018. The purposive sampling method was used in this study so that obtained 77 banking companies. Multiple linear regression with SPSS 21 was used in this study. The results showed that the mean level of human resource disclosure in ASEAN was 77%. Independent variables of firm size and auditor type have significant and positive influences on HRD. Board size has a negative and significant influence on HRD while firm age, profitability, and gender have insignificant effects. The summaries of this research are the mean level of HRD classified in high. Firm size, auditor type, and board size have significant effects on HRD while firm age, profitability, and gender have insignificant effects. The Absence of HRD level research in ASEAN countries makes this research important to study. Keywords: Human Resource Disclosure; Firm Size; Firm Age; Auditor Type; Profitability; Board Size; Gender